A new species of pitviper of the genus Bothrops (Serpentes: Viperidae: Crotalinae) from the Central Andes of South America - Timms, Juan (2019)
We describe a new species of montane pitviper of the genus Bothrops from the Cordillera Oriental of the Central Andes, distributed from southern Peru to central Bolivia. The new species can be distinguished from its congeners by the characteristic combination of a dorsal body color pattern consisting of triangular or subtriangular dark brown dorsal blotches, paired dark brown parallel occipital stripes, a conspicuous dark brown postocular stripe, the presence of canthorostrals in some specimens, prelacunal fused or partially fused with second supralabial, one scale usually separating internasals, rostral trapezoidal, two canthals oval to rounded, similar size or slightly larger than internasals, three or four medial intercanthals, eight to twelve intersupraoculars, intercanthals and intersupraoculars keeled and frequently slightly keeled, supraoculars oval, one to three suboculars, two to three postoculars, loreal subtriangular, two to six prefoveals, subfoveals absent, two or none postfoveals, one or two scales between suboculars and fourth supralabial, seven or eight supralabials, nine or eleven infralabials, 23-25 middorsal scales, 189-195 ventrals in females and 182-190 in males, 48-58 subcaudals in females and 54-63 in males, exceptionally undivided. The new species is apparently restricted to areas within Andean montane forests that are less humid and devoid of large trees.